Enhancing the Economic Value of Waste with Maggot Utilization in Village-Owned Enterprises of Arthomoro Based on Circular Economy - Darmawan, Arif; Hartono, Madi; Prayitno, Hadi; Ambya; Andayani, Sri; Lutviati, Carmelia (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
The lack of knowledge regarding organic waste management poses a significant challenge in various regions, including Pekon Panutan and Pagelaran District. Improper waste management can lead to negative impacts such as environmental pollution and health issues. One viable solution is to utilize organic waste as a valuable product through maggot cultivation. Maggots are the larvae of the Black Soldier Fly (BSF), which can decompose organic waste into high-quality compost (kasgot) used as animal feed. BUMDes Arthomoro in Pekon Panutan has the potential to enhance the economic value of waste through maggot utilization, which is supported by abundant organic waste, sufficient human resources, and community support. This community service aims to raise awareness and encourage community participation in maggot utilization. The results indicate increased residents' understanding of managing organic waste and active participation in the maggot cultivation program. The methods used include socialization and practical maggot farming training. The program received positive feedback and appreciation from community members, successfully improving participants' understanding of maggot farming as a solution for organic waste management and an opportunity to enhance economic income. This success was vital to good initial coordination, participant enthusiasm, and support from the Pekon Head and relevant stakeholders.